Didactic proposal mediated by educational digital resources to promote the use of algorithmic thinking - Parra, Camilo Andrés; Delgado Melo, Michael Steven (I+ T+ C- Research, Technology and Science, 2020)
The present study conducted a research in the fifth grade of Institución Educativa Municipal San José Bethlemitas. The purpose was to design a didactic proposal focused on promoting students’ algorithmic thinking. To accomplish this objective was necessary to carry out a research process based on George Polya’s methodology for problem-solving. This process considered four stages named: understanding the problem, shaping the plan, implementing the plan, and looking back. Initial data was collected by making use of the measurement instrument of computational thinking developed by Ma. Juan Carlos López from Universidad ICESI. It had the activities called; draw, and order the object, and get the points as a reference. To implement these activities was necessary to use Scratch 2.0, and the code time from code.org. In this way, it was possible to quantitatively demonstrate a significant change in students’ performance belonging to the experimental group. This change lets to point out the importance, and relevance of educative digital resources through a didactic sequence of computer technology area.